Deep blood vessel visualization over 10-mm depth using NIR light - Bongju Shin; Lee, Deukhee (2018 15TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS (UR), 2018)
Administering intravenous injection is a common procedure in the medical field. However, it is sometimes difficult even for professionals to administer it owing to the deep subcutaneous blood vessels of some patients. Although several devices have been developed to overcome this problem, there still exist limitations when visualizing deep blood vessels within the subcutaneous tissue. In this paper, we propose a new blood vessel visualization method using near-infrared (NIR) light. The NIR light source module of the proposed method has the shape of a picture frame with an open middle and is placed on the patient’s skin just above the target vessel and firmly fastened. Then, NIR beams, which are well-absorbed by blood, are emitted from four sides of the light source module to just below the target vessel; these NIR beams penetrate through the target vessel and an image can be acquired using an NIR camera. The image is enhanced through a series of image processing methods proposed by us to more clearly show the vessel. Through a phantom study, it is demonstrated that blood vessels up to a depth of 15 mm can be visualized. In addition, an in vivo test shows that our proposed method performs well on curved or branchy blood vessels.